PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN (KASUS BAGIAN PRODUKSI PADA PT. SARI LEMBAH SUBUR KECAMATAN GANDUANG KABUPATEN PELALAWAN) - Martua Manullang; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Problem in this research was not to achieve the realization of production in the last 4 years, the number of employees of the production are absent due to illness as well as high employee turnover akngka. As for the purpose of the research is to find out and analyze the stress of work and the performance of the production section and the employee knowing the effect of work stress on performance of employees part production at PT. Cider fertile valley Ganduang Pelalawan District. Data collection through the kusioner of 78 employees part production. Results of the study to stress employee part production has not been so good or has a fairly high level of stress in the work. For the performance of the production employees judged already, but there is still a shortage-keurangan-especially in terms of the work which is not good. Results of the analysis with SPSS programme, obtained the results that the free variables that work stress (X) have a very strong relationship to Employee Performance is variable (Y)Keywords: job stress, employee performance, PT Sari fertile valley Ganduang Pelalawan District